Local self government as a factor for the formation of social practice in cultural heritage preservation - Marietta Askarbievna Bolokova (Вестник Майкопского государственного технологического университета)
In recent decades ecological changes, emergence of negative manifestations of technogenic, anthropogenic nature, transformations in the social and economic space have defined the relevance of public discourses in defence of the domestic cultural heritage. Social self-government plays an important role in preserving historical and cultural traditions of our society. The level of local self-government is a starter for social and economic development of all regions of our country, including the impact on the state of cultural and social climate. Preserving cultural heritage in the regions is one of the most urgent and important issues. Lack of adequate funding, weak interaction within the system of the society - municipal authorities - business, often does not allow to carry out the necessary level of preservation of the historical and cultural past. Meanwhile, the effectiveness of local self-government influences the possibility of solving the problems of preservation and use of such facilities. The aim of the research is to find effective ways to interact with local authorities, business and the public, in the field of creating an effective system for saving and using cultural heritage objects. A comparative and structural-functional approach have been used in the research as a basic methodology. Systematic review of the mechanisms of the work of state structures, allows to proceed to the analysis of public civil institutions. The main result of the work is theoretical revision of the acute problem of preservation of forms of cultural heritage in the conditions of local self-government. The most promising ways to develop the practice of local authorities, to address issues of preservation and rational use of historically significant cultural objects have been identified. It has been concluded that applying the cluster technology for the development of the social environment as the basis for the solution of the complex issue of preservation of cultural and historical heritage is prospective. The main aspects formulated in the research process can be used as a theoretical and methodological basis for deeper scientific research in this field.